Analysis on the change of the death and missing in Luding earthquake and the impact of geological disaster on them - Jingjing Liu; Na Gao (地震科学进展, 2024)
This paper collected the data of death and loss of contact in Luding MS6.8 earthquake, quantitatively analyzed the characteristics of the number of deaths and loss of contacts over time, and compared with typical destructive earthquakes in recent 10 years. Combing the actual emergency rescue work, this paper sort out and summarized the main reasons, systematically analyzed the impact of geological disasters on personnel mortality and loss of connection rate, discussed the characteristics of earthquake disasters and disaster relief in mountainous areas. At the same time, we propose suggestions for the verification and submission capabilities of earthquake disaster information and the improvement of personnel search and rescue capabilities in complex mountainous environments.